The Impact of Financial Redundancy on Corporate Social Responsibility Performance: Evidence From Chinese Listed Firms - He, Ling; Gan, Shengdao; Zhong, Tingyong (Frontiers in Psychology, 2022)
This study examines the impact of financial redundancy on corporate social responsibility (CSR) based on a sample of Chinese listed firms from 2010 to 2020. The results indicate that financial redundancy has a significant positive effect on CSR. However, financially redundant resources are not balanced in terms of how they encourage firms to undertake different dimensions of social responsibility; specifically, firms actively take social responsibility toward shareholders and the public but take less responsibility for employees and the environment. The incentive for firms with financially redundant resources to promote CSR initiatives is attributable to their high level of social awareness and pursuit of reputation. Consistent with their motives, our economic consequence analysis reveals that the incremental effect of CSR driven by financial redundancy improves corporate reputation but has no enhancement effect on corporate performance. Finally, our extended analysis reveals that the relative impact of financial redundancy on CSR depends on several organizational variables that influence a firm’s preferences for CSR investments. The positive impact of financial redundancy on CSR is stronger among firms with high managerial career concerns and firms in regions with high market competition. This research provides a necessary structure for future CSR studies to follow. By delving deeply into the relationship between financial redundancy and CSR, it enables scholars to better address the critical management question of whether wealthy firms do more good for society compared to those that are less wealthy.